Levulinic acid production from lignocellulosic biomass using hy zeolite supported chromium catalyst in ionic liquid [electronic resource] - Nazlina Ya'aini, 1986- (2012)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2012